2013
DOI: 10.9734/bjecc/2013/2492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Petroleum Crude Oil on Mineral Nutrient Elements, Soil Properties and Bacterial Biomass of the Rhizosphere of Jojoba

Abstract: Aims: This study is to evaluate the effect of petroleum crude oil contaminated soil on the mineral nutrient elements, soil properties and bacterial biomass of the rhizosphere of jojoba plants (Simmodsia chinensis). Methodology: A pot experiment was carried out. The soil was treated with different levels of crude oil: 1, 2 and 3% v/w either alone or in combination with inorganic fertilizers. Results: Malondialdehyde (MDA) concentration increased in jojoba leaves when grown in petroleum oil polluted soil especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 56 publications
4
13
0
2
Order By: Relevance
“…The data from this study revealed appreciable increases in organic matter contents following the increase in the level of applied petroleum oil against the control soils, thereby agreeing with the reports of [30,31,32] who reported a surge in organic matter content of contaminated soil. The observed response to increase in the level of crude oil spilled was thereafter followed by a remarkable gradual decrease in the percentage organic matter with time (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The data from this study revealed appreciable increases in organic matter contents following the increase in the level of applied petroleum oil against the control soils, thereby agreeing with the reports of [30,31,32] who reported a surge in organic matter content of contaminated soil. The observed response to increase in the level of crude oil spilled was thereafter followed by a remarkable gradual decrease in the percentage organic matter with time (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The toxicity of the used hydrocarbon substances to microorganisms inhabiting the investigated soil type might be summarized as follows: diesel > new oil > waste oil > petrol. Ramadass et al ( 2015 ) suggested that used oils are the most hazardous mainstream categories of environmental pollutants, posing a major threat to the environment and public health because they are responsible for immobilization of nutrients and lowering of soil pH (Shukry et al 2013 ). However, this partially remains in contrast to our results, as we observed a less toxic effect posed by waste oil rather than by new oil in relation to DHA and CMC.…”
Section: Discussionmentioning
confidence: 99%
“…These unguided practices of indiscriminate disposal have worsened the rate at which used engine oils spread and contaminate the soil and water around the town. Researches has showed that used oil is less viscous than unused oil; as such when improperly disposed into the soil, absorbs to the soil particles, reducing porosity and therefore reduces aeration of soil [26].…”
Section: Introductionmentioning
confidence: 99%